2019
DOI: 10.1002/adsc.201900874
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Mediated Sulfenylation‐Annulation Cascade of Alkyne Tethered Cyclohexadienones

Abstract: A mild and facile method to access sulfenylated dihydrochromenones via a visible light mediated thiol-yne/conjugate addition cascade of alkyne-tethered cyclohexadienones, using cheap and readily available organic photoredox catalyst (Eosin Y) is demonstrated. The utility and sustainability of the protocol were further justified by the high yields, excellent diastereoselectivities, broad substrate scope, gram scale synthesis, green chemistry metrics (atom economy and efficiency) and further synthetic transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Shortly thereafter, Nair et al described a diastereoselective visible-light mediated cascade of cyclohexadienones 278 with alkyne tethers (Scheme 43). [116] Good yields were reported, as was good functional group tolerance. This account relies on Eosin Y as the organic photocatalyst, and boasts an array of thiophenols/thiols as radical precursors, with electron donating and electron withdrawing groups in para-and ortho-positions tolerated for the aromatic thiols.…”
Section: State Of the Artmentioning
confidence: 97%
See 2 more Smart Citations
“…Shortly thereafter, Nair et al described a diastereoselective visible-light mediated cascade of cyclohexadienones 278 with alkyne tethers (Scheme 43). [116] Good yields were reported, as was good functional group tolerance. This account relies on Eosin Y as the organic photocatalyst, and boasts an array of thiophenols/thiols as radical precursors, with electron donating and electron withdrawing groups in para-and ortho-positions tolerated for the aromatic thiols.…”
Section: State Of the Artmentioning
confidence: 97%
“…The authors were also able to demonstrate the applicability to gram scale synthesis, and reported favourable green chemistry metrics (atom economy, and efficiency). A publication [117] Shortly thereafter, Nair et al described a diastereoselective visible-light mediated cascade of cyclohexadienones 278 with alkyne tethers (Scheme 43) [116]. Good yields were reported, as was good functional group tolerance.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic potential of Eosin Y in mediating C−S bond formation was further explored by Nair and co‐workers [157] . They have reported a blue light induced, Eosin Y mediated sulfenylation of alkyne tethered cyclohexadienones ( 139 ) followed by cascade annulation via conjugate addition to yield sulfenylated dihydrochromenones ( 140 ).…”
Section: Sulfenylationmentioning
confidence: 99%
“…Finally, abstraction of proton from thiol resulted into desired sulfenylated dihydrochromenones ( 140 ) along with thienyl radical ( 5 F ) (Scheme 47). [157] …”
Section: Sulfenylationmentioning
confidence: 99%